Atwood's Machine and Electromagnetic Induction: A Real Quantitative Experiment to Analyze Students' Ways of Reasoning. Issue 2 (2022) - Bozzo, Giacomo; Michelini, Marisa; Bonanno, Assunta; Stefanel, Alberto
No abstract available